Changing the composition of the group hydrocarbons of diesel fractions in the process of hydrotreating; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Krivtsova N. I. Nadezhda Igorevna; Baklashkina K.; Sabiev Sh.; Krivtsov E.; Syskina A. A. Anna Aleksandrovna (Latest Research in Hydrocarbon Refining, 2016)
Title screen